1997
DOI: 10.1023/a:1007979502754
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Rabies enzootics in southern Africa are associated with two genetically distinct groups of viruses, thought to be adapted to two different sets of host species. The virus groups are referred to as the canid biotype (infecting carnivores of the family Canidae) and the viverrid biotype (infecting carnivores of the subfamily Viverrinae). Cross- or spillover infections of one biotype into the host range of the other are thought to occur from time to time. However, very little is known about this phenomenon and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Although Africa-1 and Africa-2 lineages have been documented in several domestic and wild carnivore species, domestic dogs are virtually the only population essential for maintaining canid variants in some parts of Africa [ 47 ]. Conversely, wild canids have been suggested to contribute to the sustainment of canine rabies cycles in specific geographic locations in South Africa, Namibia and Zimbabwe [ 32 , 48 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although Africa-1 and Africa-2 lineages have been documented in several domestic and wild carnivore species, domestic dogs are virtually the only population essential for maintaining canid variants in some parts of Africa [ 47 ]. Conversely, wild canids have been suggested to contribute to the sustainment of canine rabies cycles in specific geographic locations in South Africa, Namibia and Zimbabwe [ 32 , 48 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…These civet sequences are further divided into two subclades, one with dates of origin ranging from 1981 to 2009 and locations including RSA and Zimbabwe, the other restricted to three sequences from Zimbabwe in the early 1990s. These inferred evolutionary relationships raise the possibility of maintenance of RABV within civet populations for up to 50 years, with recent spill-over into other wild canids and dogs [41]. The tree topology not only indicates that the African civets have been exposed to dog-maintained RABVs for as long as the dog variant has been maintained in this species in this region, but also that this long term exposure could have led to the establishment of originally dog-maintained RABV in African civet populations.…”
Section: Discussionmentioning
confidence: 96%
“…In Zimbabwe, the African civet is not considered a major host for RABV (it only accounts for about 1.5% of all confirmed wildlife cases), and the epidemiology suggests that most of these cases are detected during epidemics of jackal rabies. Initial monoclonal antibody typing studies of African civet viruses [18,41,45] showed that they were indistinguishable from jackal viruses (Africa 1, canid rabies biotype), but more recent data supported the notion that African civet populations may be capable of supporting the maintenance of enzootic mongoose rabies [17]. Although Haydon 2012 discussed and highlighted the challenges of identifying reservoirs of RABV infection, Lembo et al (2008) [46] demonstrated that persistence of infection in a population is a prerequisite for identifying reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Typical examples include the cases in Europe where rabies evolved from domestic dogs to raccoon dogs and foxes ( Bourhy et al, 1999 ), the emergence of fox rabies in Colombia and Brazil ( Bernardi et al, 2005 ; Paez et al, 2005 ; Carnieli et al, 2008 ), and wildlife rabies in the United States ( Guerra et al, 2003 ). Other spillover events of rabies from dogs to wildlife have been observed in southern Africa ( Nel et al, 1997 ; Sabeta et al, 2003 , 2007 ; Zulu et al, 2009 ), Puerto Rico ( Krebs et al, 2003 ; Nadin-Davis et al, 2008 ), and Turkey ( Johnson et al, 2003 ). Because wildlife RABV variants can also transmit to unvaccinated dogs, thus entering urban environments, as has been observed in former Yugoslavia ( Stankov, 2001 ).…”
Section: Discussionmentioning
confidence: 99%